Validity of simplified protocols to estimate glomerular filtration rate using iohexol clearance. - James, T; Lewis, A; Tan, G; Altmann, P; Taylor, R; Levy, J (2007)
BACKGROUND: Iohexol clearance is an accurate and precise exogenous marker of glomerular filtration rate (GFR), but protocols are generally lengthy or require multiple sampling. Shorter or simpler protocols would be more practicable. METHODS: Two clearance estimates, two weeks apart, were undertaken in 11 healthy individuals and 26 diabetic patients with minimal to moderate renal impairment (chronic kidney disease stages 1-3). Blood specimens withdrawn at 60, 90, 120, 150, 180 and 240 min post-iohexol were analysed for iohexol. RESULTS: Visit 1 demonstrated excellent correlation with visit 2 (slope 1.00, confidence interval [CI] 0.88 to 1.13, intercept 0.94 mL/min/1.73 m(2), CI -9.9 to 11.8, P=0.43). The within-individual coefficient of variation (CV) of the 240 min reference method was 5.4% at a mean GFR of 84.1 mL/min/1.73 m(2). Single point estimates between 120 and 240 min had CVs of 4.5-7.0%, and did not differ from the reference method CV by more than 2.0 mL/min/1.73 m(2). Two and three point estimates in the interval 60-120 min post iohexol injection offered no advantages over these single-point estimates and overestimated at lower GFRs. CONCLUSIONS: An iohexol clearance estimate of GFR derived from a single sample taken between 2 to 4 h after infusion may provide a suitable tool for routine clinical use.